Islamic Educational Marketing Management - Nasrullah, Nasrullah; Tamam, Khoirit; Hidayat, Rahmat (International Conference on Islamic Studies, 2021)
In education, the most important component should make a real contribution to improving human resources (HR). Management of quality education cannot be separated from management in general, namely: planning, organizing, directing and controlling. Quality of education is something that is considered important by customers/users of educational services, in Islamic educational institutions as well as efforts to improve Islamic education in achieving predetermined standards of the quality. Islamic educational institutions should show better quality in the future, both physical and non-physical, because from this, Islamic educational institutions can still gain the trust of the public in general, so that educational institutions get customers who are tailored to the target and that is where educational marketing is needed to increase consumer interest from an educational institution.